2014
DOI: 10.3171/2014.2.spine13794
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive versus open transforaminal lumbar interbody fusion: comparison of clinical outcomes among obese patients

Abstract: Object Minimally invasive (MI) transforaminal lumbar interbody fusion (TLIF) has been demonstrated in previous studies to offer improvement in pain and function comparable to those provided by the open surgical approach. However, comparative studies in the obese population are scarce, and it is possible that obese patients may respond differently to these two approaches. In this study, the authors compared the clinical benefit of open and MI TLIF in obese patients. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 42 publications
1
59
0
4
Order By: Relevance
“…Although EBL differences across randomized studies did not reach clinically meaningful levels of ≥ 750 mL, one of the randomized studies did find a significantly 1002 WJO|www.wjgnet.com [43] 168. [44] 159.2 ± 21.7 142.8 ± 22.5 399.8 ± 125.8 517.0 ± 147.8 0% 0% 9.3 ± 2.6 12.5 ± 1.8 Wang et al [45] 139.0 ± 27.0 143.0 ± 35.0 291.0 ± 86.0 652.0 ± 150.0 12% 19% --Cohort studies Wong et al [46] 173 309 115 485 12% 13% 2.8 4.4 Zhang et al [47] 120 ± 35 115 ± 28 250 ± 75 650 ± 150 0% 3% --Villavicencio et al [48] 223 ± 68 215 ± 60 163 ± 131 367 ± 298 11% 13% 3.0 ± 2.3 4.2 ± 3.5 Lee et al [49] 166 ± 52 182 ± 45 161 ± 51 447 ± 519 1% 0% 3.2 ± 2.9 6.8 ± 3.4 Terman et al [50] --100 450 --2.0 3.0 Cheng et al [51] 245 ± 73 279 ± 15 393 ± 284 536 ± 324 0% 12% 4.8 ± 1.8 6.1 ± 1.8 Liang et al [52] 127 ± 60 96 ± 46 194 ± 86 357 ± 116 ----Yang et al [53] 175 ± 35 177 ± 30 362 ± 177 720 ± 171 7% 2% 4.0 ± 1.3 7.1 ± 1.0 Gu et al [54] 196 ± 28 187 ± 23 248 ± 94 576 ± 176 5% 3% 9.3 ± 3.7 12.1 ± 3.6 Wang et al [55] 145 ± 27 156 ± 32 264 ± 89 673 ± 145 10% 7% 10.6 ± 2.5 14.6 ± 3.8 Zairi et al [56] 170 186 148 486 3% 3% 4.5 5.5 Seng et al [57] 185 ± 9 166 ± 7 127 ± 46 405 ± 80 ----Pelton et al [58] 112 ± 33 185 ± 34 125 ± 76 275 ± 99 --2.0 ± 0.7 3.0 ± 1.1 Singh et al [59] 116 ± 28 186 ± 31 124 ± 92 380 ± 191 --2.3 ± 1.2 2.9 ± 1.1 Brodano et al [60] 144 102 230 620 3% 9% 4.1 7.4 Zou et al [61] 150 ± 41 175 ± 37 131 ± 74 318 ± 177 0% 0% 7.5 ± 2.7 9.3 ± 4.2 Peng et al [62] 216 171 150 681 --4.0 6.7 Archavlis et al [63] 220 ± 48 190 ± 65 185 ± 140 255 ± 468 13% 4% 7.0 11.0 Dhall et al [64] 199 237 194 505 0% 5% 3.0 5.5 Schizas et al [65] --456 961 17% 6% 6.1 8.2 Adogwa et al [66] 300 210 200 295 0% 0% 3.0 5.0 Niesche et al [67] 140 130 150 380 0% 11% 5.0 10.0 Lau et al [68] reduced transfusion need between MIS and open TLIF [44] . LOS was found to be significantly reduced in MIS TLIF by almost three days, however all of the studies originated from Chinese hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although EBL differences across randomized studies did not reach clinically meaningful levels of ≥ 750 mL, one of the randomized studies did find a significantly 1002 WJO|www.wjgnet.com [43] 168. [44] 159.2 ± 21.7 142.8 ± 22.5 399.8 ± 125.8 517.0 ± 147.8 0% 0% 9.3 ± 2.6 12.5 ± 1.8 Wang et al [45] 139.0 ± 27.0 143.0 ± 35.0 291.0 ± 86.0 652.0 ± 150.0 12% 19% --Cohort studies Wong et al [46] 173 309 115 485 12% 13% 2.8 4.4 Zhang et al [47] 120 ± 35 115 ± 28 250 ± 75 650 ± 150 0% 3% --Villavicencio et al [48] 223 ± 68 215 ± 60 163 ± 131 367 ± 298 11% 13% 3.0 ± 2.3 4.2 ± 3.5 Lee et al [49] 166 ± 52 182 ± 45 161 ± 51 447 ± 519 1% 0% 3.2 ± 2.9 6.8 ± 3.4 Terman et al [50] --100 450 --2.0 3.0 Cheng et al [51] 245 ± 73 279 ± 15 393 ± 284 536 ± 324 0% 12% 4.8 ± 1.8 6.1 ± 1.8 Liang et al [52] 127 ± 60 96 ± 46 194 ± 86 357 ± 116 ----Yang et al [53] 175 ± 35 177 ± 30 362 ± 177 720 ± 171 7% 2% 4.0 ± 1.3 7.1 ± 1.0 Gu et al [54] 196 ± 28 187 ± 23 248 ± 94 576 ± 176 5% 3% 9.3 ± 3.7 12.1 ± 3.6 Wang et al [55] 145 ± 27 156 ± 32 264 ± 89 673 ± 145 10% 7% 10.6 ± 2.5 14.6 ± 3.8 Zairi et al [56] 170 186 148 486 3% 3% 4.5 5.5 Seng et al [57] 185 ± 9 166 ± 7 127 ± 46 405 ± 80 ----Pelton et al [58] 112 ± 33 185 ± 34 125 ± 76 275 ± 99 --2.0 ± 0.7 3.0 ± 1.1 Singh et al [59] 116 ± 28 186 ± 31 124 ± 92 380 ± 191 --2.3 ± 1.2 2.9 ± 1.1 Brodano et al [60] 144 102 230 620 3% 9% 4.1 7.4 Zou et al [61] 150 ± 41 175 ± 37 131 ± 74 318 ± 177 0% 0% 7.5 ± 2.7 9.3 ± 4.2 Peng et al [62] 216 171 150 681 --4.0 6.7 Archavlis et al [63] 220 ± 48 190 ± 65 185 ± 140 255 ± 468 13% 4% 7.0 11.0 Dhall et al [64] 199 237 194 505 0% 5% 3.0 5.5 Schizas et al [65] --456 961 17% 6% 6.1 8.2 Adogwa et al [66] 300 210 200 295 0% 0% 3.0 5.0 Niesche et al [67] 140 130 150 380 0% 11% 5.0 10.0 Lau et al [68] reduced transfusion need between MIS and open TLIF [44] . LOS was found to be significantly reduced in MIS TLIF by almost three days, however all of the studies originated from Chinese hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Although decompressive lumbar laminectomy is a relatively straightforward spinal operation, there exists a steep learning curve associated with microscopeassisted tubular spinal surgery [68] , which could be one important factor accounting for the differences in operative times between the two techniques. With the growing popu larity of minimally invasive approaches and the growing number of younger surgeons performing minimally 1001 WJO|www.wjgnet.com [43] 2011 TLIF LSS, herniation, spondylolisthesis 41 38 Shunwu et al [44] 2010 TLIF Degenerative lumbar disease 32 30 Wang et al [45] 2011 TLIF Failed discectomy and decompression 25 27 Cohort studies Wong et al [46] 2014 TLIF FBSS, DDD, spondylolisthesis 144 54 Zhang et al [47] 2013 TLIF DDD 82 76 Villavicencio et al [48] 2010 TLIF LSS, DDD ± herniation, spondylolisthesis 76 63 Lee et al [49] 2012 TLIF LSS, DDD, herniation, spondylolisthesis 72 72 Terman et al [50] 2014 TLIF DDD, LSS, spondylolisthesis, herniation 53 21 Cheng et al [51] 2013 TLIF Spondylosis/listhesis, foraminal stenosis 50 25 Liang et al [52] 2011 TLIF Degenerative lumbar instability 45 42 Yang et al [53] 2013 TLIF Lumbar degenerative diseases 43 104 Gu et al [54] 2014 TLIF Degenerative conditions 43 38 Wang et al [55] 2010 TLIF Spondylolisthesis 42 43 Zairi et al [56] 2013…”
Section: Discussionmentioning
confidence: 99%
“…Wong et al [10] compared 144 MI TLIF with 54 standard TLIF patients and found statistically significant benefits for MI TLIF in operating room time, blood loss, primary infection rates, secondary medical complications, LOS, transfusion need, hospital costs, short-term and long-term pain outcomes, and short-term and long-term ODI scores. Terman et al [8] retrospectively reviewed his results at a single institution in obese patients undergoing MI TLIF ( n = 53) and S TLIF ( n = 21) and concluded that both procedures had good results, similar to those in nonobese patients. Other studies with fewer patients enrolled had results generally favoring the MI TLIF technique.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies comparing open TLIF to MI-TLIF in obese patients have demonstrated comparable short-term outcomes regarding pain relief and functional improvement [19,20]. Furthermore, MI-TLIF has been reported to be associated with either decreased or equivalent rates of perioperative complications when compared to open TLIF [21][22][23].…”
Section: Introductionmentioning
confidence: 99%